The Collaborative Seismic Earth Model: Generation 1. Issue 9 (12th May 2018) - Fichtner, Andreas; van Herwaarden, Dirk‐Philip; Afanasiev, Michael; Simutė, Saulė; Krischer, Lion; Çubuk‐Sabuncu, Yeşim; Taymaz, Tuncay; Colli, Lorenzo; Saygin, Erdinc; Villaseñor, Antonio; Trampert, Jeannot; Cupillard, Paul; et al.
Abstract: We present a general concept for evolutionary, collaborative, multiscale inversion of geophysical data, specifically applied to the construction of a first‐generation Collaborative Seismic Earth Model. This is intended to address the limited resources of individual researchers and the often limited use of previously accumulated knowledge. Model evolution rests on a Bayesian updating scheme, simplified into a deterministic method that honors today's computational restrictions. The scheme is able to harness distributed human and computing power. It furthermore handles conflicting updates, as well as variable parameterizations of different model refinements or different inversion techniques. The first‐generation Collaborative Seismic Earth Model comprises 12 refinements from full seismic waveform inversion, ranging from regional crustal‐ to continental‐scale models. A global full‐waveform inversion ensures that regional refinements translate into whole‐Earth structure. Plain Language Summary: Modern geophysical data are often characterized by their distribution across multiple spatial scales, meaning that high‐density local or regional deployments are complemented by coarser global‐scale recordings. Examples include data from seismic, electromagnetic, or Global Positioning System (GPS) measurements. While data volumes increase steadily, the actually usable amount of information is limited by the available human and computing power of individual researchers. Here we present a new framework that supports collaborative and evolutionary inversion of geophysical data, where prior knowledge from earlier data can be incorporated. We exemplify our method with a seismological application, that is, the construction of a Collaborative Seismic Earth Model of the 3‐D internal structure of our planet. Key Points: We present a framework for evolutionary, community‐driven, multiscale inversion of geophysical data This is illustrated by the construction of a Collaborative Seismic Earth Model The first‐generation model includes 12 regional refinements based on full-waveform inversion